Social Support In Restoring Sight After Cataract Surgery For The Poor In Ampang Hospital Malaysia - Azlina Mokhtar; Noor Fadzilah Zulkifli; Nazefah Abdul Hamid; Nor Azila Noh (Bharati Vidyapeeth University, Pune, India, 2024)
To address the accessibility of funds from social support groups in order to enable the poor to undergo cataract operation and restore their eyesight. Awareness on the availability of fund among the poor is still low, thus highlighting the need for promotion of the facility. All data of patient who underwent cataract surgery with intraocular lens implanted from January 2012 to June 2014 in Ampang Hospital, Malaysia were retrieved. The records showed that 102 patients were funded for cataract surgery and had intraocular lens implanted. Almost all of these patients had low vision to near blindness prior to surgery but achieved excellent visual acuity post-operation. Restoring sight from cataract is a necessity for these patients since it will lead to a more productive life and increase the quality of life. Up to this date, various social support groups have contributed significantly to enable the poor to access advanced health care services. With the cooperation of Ampang Hospital and the Social Welfare Department of Malaysia, a simple method is needed to determine the eligibility of funding among poor patients who are required to undergo cataract surgery and intraocular lens implantation. The financial contributions from the various social support groups and non-governmental organizations are noble and sustainable. Restoring eyesight contributes to better quality of life amongst the underprivileged population.